ANALISIS POTENSI PENJUALAN SEPEDA MOTOR LISTRIK PRODUK HONDA DI INDONESIA - Zafira Az Zahra; Inaya Amalia Putri; Syamsul Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The electric motorcycle has captured the attention of various groups, including students, due to its combination of unique design, quality that matches the price, and environmental friendliness by not emitting smoke. Increased awareness of environmental impact has driven interest in this vehicle in the market. Factors such as energy efficiency, low operational costs, and user convenience are also the primary reasons for its popularity among students. Thus, electric motorcycles offer a sustainable and appealing transportation solution for contemporary consumers, especially in campus and urban environments